Leber Hereditary Optic Neuropathy: Do Folate Pathway Gene Alterations Influence the Expression of Mitochondrial DNA Mutation? - A Aleyasin; M Ghazanfari; M Houshmand (Tehran University of Medical Sciences, 2010)
Background: Leber hereditary optic neuropathy (LHON) is an inherited form of bilateral optic atrophy leading to the loss of central vision.  The primary cause of vision loss is mutation in the mitochondrial DNA (mtDNA), however, unknown secondary genetic and/or epigenetic risk factors are suggested to influence its neuropathology.  In this study folate gene polymorphisms were examined as a possible LHON secondary genetic risk factor in Iranian patients. Methods: Common polymorphisms in the MTHFR (C677T and A1298C) and MTRR (A66G) genes were tested in 21 LHON patients and 150 normal controls. Results:  Strong associations were observed between the LHON syndrome and C677T (P= 0.00) and A66G (P= 0.00) polymorphisms.  However, no significant association was found between A1298C (P =0.69) and the LHON syndrome. Conclusion: This is the first study that shows MTHFR C677T and MTRR A66G polymorphisms play a role in the etiology of the LHON syndrome.  This finding may help in the better understanding of mechanisms involved in neural degeneration and vision loss by LHON and hence the better treatment of patients.